The VIKOR Method to Support the Effectiveness of Decisions in Determining Work Incentive Recipients. (March 2019) - Mesran, M; Siregar, Dodi; Darma Nasution, Surya; Hafni Sahir, Syafrida; Mohd Diansyah, Tengku; Agustina, Ika; Supriyanto, S; Wardayani, W; Astuti Hasibuan, Nelly; Shinta Wulandari Lubis, Dewi; Anas, Amril; Ade Sitorus, Sunday; et al.
Abstract: Giving Incentives is a way given by the company in increasing the work motivation of its employees. Providing incentives to employees has stages that must be passed by the leadership in producing a better and effective decision. In order for the decisions produced are not objective, the leader needs a process of calculating the performance index of his employees. In this study, the application of VIKOR is needed in managerial decision support systems. It is intended that the decisions produced are no longer of objective value to employees who are given salary incentives.